2009
DOI: 10.1063/1.3136904
|View full text |Cite
|
Sign up to set email alerts
|

The making of ferromagnetic Fe doped ZnO nanoclusters

Abstract: In this letter, the authors present a study of the energetics and magnetic interactions in Fe doped ZnO clusters by ab-initio density functional calculations. The results indicate that defects under suitable conditions can induce ferromagnetic interactions between the dopant Fe atoms whereas antiferromagnetic coupling dominates in a neutral defect-free cluster. The calculations also reveal an unusual ionic state of the dopant Fe atom residing at the surface of the cluster, a feature that is important to render… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 18 publications
3
28
0
Order By: Relevance
“…The other possibility is surface-vacancy-induced ferromagnetism. 18 18,39 This will occur mostly in the surface region of the nanoparticles, where the probability of the creation of vacancies is higher. 18 Based on the earlier theoretical study 40 and XAS measurements 41 of nanoparticles, we suggest that the presence of the Fe 3+ ͑O h ͒ ions is due to excess oxygen at the surface of the nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The other possibility is surface-vacancy-induced ferromagnetism. 18 18,39 This will occur mostly in the surface region of the nanoparticles, where the probability of the creation of vacancies is higher. 18 Based on the earlier theoretical study 40 and XAS measurements 41 of nanoparticles, we suggest that the presence of the Fe 3+ ͑O h ͒ ions is due to excess oxygen at the surface of the nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Thus hopping induced interaction between the dopant Mn atoms stabilizes the tendency of FM for this system, similar to our previous observation for Fe doped ZnO cluster with the same defect state. 12 In this context, an experimental report has also pointed out that deficiency of electrons can induce FM in Mn doped ZnO quantum dots. 3 A calculation by Feng et al in the framework of TDDFT also claims that double exchange mechanism induced by optical excitation can stabilize FM in Mn doped ZnO quantum dots.…”
Section: B Effect Of Vacancymentioning
confidence: 99%
“…In a recent work, using GGA+ U on Fe doped ZnO clusters we have shown that defects under suitable conditions can induce ferromagnetic interactions between the dopant Fe atoms, whereas AFM coupling dominates in a neutral defect-free cluster. 12 In addition, there are several calculations that suggest that ZnO nanocluster may be ferromagnetic without TM dopants. Schoenhalz et al 13 have proposed that the surface states promoted by extended defects ͑e.g., grain boundaries͒ may play an important role in mediating ferromagnetic interaction in such materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current interest in such magnetic nano-particle systems is motivated by unique electronic structures and magnetism at the surfaces of the nano-particles which are different from the inner core region. In the nano-particle form, the structural and electronic properties are modified by surface defects such as Zn and O vacancies with broken chemical bonds and charge imbalance, which may mediate or modify exchange coupling between the doped atoms [7]. For example, high-valence (3+ and 4+) Mn and Co ions are found to be present in the surface of paramagnetic (Mn,Co)-codoped ZnO nano-particles [8], probably due to the formation of Zn vacancies (V Zn ) in the surface region.…”
Section: Introductionmentioning
confidence: 99%